Analisis Gaya Bahasa Pidato Menteri Kesehatan Budi Gunadi Sadikin Serta Rekomendasinya Sebagai Bahan Ajar Pidato Persuasif Tingkat Smp - Arrasyid, Abdu Maulana; Pratiwi, Wieneke Dinar; Meliasanti, Ferina (Peneliti.net, 2024)
The aims of this study were (1) to describe the speech of the Minister of Health Budi Gunadi Sadikin, and (2) to describe the recommendations for the research results of the language style of the Minister of Health Budi Gunadi Sadikin's speech as teaching material for persuasive speeches at the junior high school level. The theory used in this study is Gorys Keraf's language style theory (2009). This research methodology uses a qualitative approach with descriptive methods. The subject of this study is the Minister of Health Budi Gunadi Sadikin who serves as Minister of Health from 2020. The object of this research is the language style of the Minister of Health Budi Gunadi Sadikin's speech at the Revitalitation & Transformation Toward Center of Excellence activity at Karawang Hospital and National Working Meeting 2023